Solar access in urban planning : Early-stage assessment of sunlighting and daylighting - Czachura, Agnieszka (Department of Architecture and Built Environment, Lund University, 2026)
The densification of European cities presents a critical challenge for solar access, particularly in high-latitude Nordic climates. While urban planning in Sweden defines the geometric boundaries of future buildings, there is no statutory requirement to evaluate the resulting solar access at this stage. At later design stages, the Swedish Building Regulations (BBR) mandate daylighting provision, whereas sunlighting prescriptions have recently been removed. To safeguard solar access early on, urban planning requires assessment methods aligned with the low level of detail inherent to early design, as conventional climate-based metrics require indeterminate inputs. Framed through the lens of habitability, this thesis investigated early-stage metrics capable of assessing the geometric capacity of neighbourhood designs to deliver daylighting and sunlighting into the urban fabric. Using a sequential mixed-methods approach, the research identified, calibrated, and evaluated early-stage solar access indicators. The indoor daylighting indicator—the Vertical Sky Component (VSC)—was calibrated against building standards to generate bespoke compliance targets. Simultaneously, the indoor sunlighting indicator was evaluated through simulations and in situ interviews to provide empirical evidence for sunlight provision in Sweden. Regarding daylighting, the research demonstrated that compliance with modern standards (BBR and EN 17037) using the ubiquitous heuristic (VSC ≥ 27%) is conditional and often unattainable. Because compliance depends heavily on internal room geometry and Window-to-Floor Ratio (WFR), the study developed bespoke, design-based VSC thresholds for the Swedish context. These dynamic targets can be incorporated into digital urban planning tools to refine early assessments and support late-stage compliance. Regarding sunlighting, empirical investigations confirmed that direct indoor sunlight is a highly valued amenity, though it carries inherent risks of visual and thermal discomfort. In high-latitude contexts with low solar angles, the findings indicate that adjustable shading devices should be considered a compulsory residential design element. To prevent sunlight scarcity and ensure baseline habitability, the research proposes a minimum regulatory prescription: disallowing apartments oriented exclusively toward the northern sector. Ultimately, the indicators and methodologies proposed in this thesis provide an empirically derived framework for early-stage solar access assessment, ensuring that urban densification does not compromise the fundamental habitability of future residential environments.
Keywords: habitability; urban densification; daylighting compliance; indoor sunlighting; building performance simulation (BPS); EN 17037; occupant satisfaction; BBR